Establishment of lactate-metabolism-related signature to predict prognosis and immunotherapy response in patients with colon adenocarcinoma - Zou, Zhengrong; Chai, Yongjie; Li, Qi; Lin, Xuan; He, Qingfang; Xiong, Qiusheng (Frontiers in Oncology, 2022)
The outcome of colon adenocarcinoma (COAD) patients remains dismal and lactate metabolism has been characterized to promote tumor development and immune evasion. Based on the above background, it is worthwhile to explore novel prognostic and therapeutic biomarkers for COAD patients from the aspect of lactate metabolism. Above all, 228 available lactate-metabolism-related genes (LMRGs) were acquired and the panoramas of copy number variation and expression difference of mRNA levels between colon normal and tumor samples were investigated among these LMRGs. Importantly, eight overall survival-involved LMRGs were then distinguished by means of univariate Cox regression analysis together GSE40967 and TCGA-COAD datasets. Subsequently, prognostic risk scores were established integrating seven OS-related LMRGs by Lasso cox regression analysis in GSE40967 set, and then verified in TCGA-COAD cohort. From the comprehensive analyses, COAD patients with high-risk had comparatively more inferior survival probability in all populations of the study, and they tended to have severer clinicopathological features with the risk score increasing. Moreover, by integrating age, T, AJCC stage and risk score, we constructed a prognostic nomogram which strikingly demonstrated great prediction effectiveness for OS of COAD patients. Furthermore, the potential effect of various risk score on tumor immune was assessed from enrichment of immune-related pathways, tumor-infiltrating immune cells and expression levels of immune checkpoints separately. And we could draw a conclusion that COAD patients with higher lactate-metabolism-related risk scores may acquire immunosuppressive tumor microenvironment which subsequently lead to immune escapes and poor prognoses. Conclusively, all findings in the present study illustrated great prognostic value of the lactate-metabolism-related risk signature, providing more in-depth insights into the indispensable function of lactate metabolism in prognosis and tumor immunity of COAD.